From the room to the square: motivation, mediation and Vigotsky to understand the behavior - Magalhães, Cláudio Márcio (2018)
Motivation is a key subject for the discipline of Consumer Behavior in Advertising and Propaganda courses, despite the fact that its conceptualization is approached by several theories that may sometimes be contradictory in addition to alumni aversion to the theoretical study. This work proposes an approach that leads one to build one’s own understanding, without underestimating different perspectives. A series of activities were developed ranging from traditional to innovative by means of an active methodology, which considers the student the center of his or her own learning. As a reference, the research was based on the work of the Russian psychologist and educator Lev Vigotsky in an attempt to become an incentive for similar methodologies that link the school environment with the public space, the interior of the classroom with the subject’s interior.